THE ROLE OF DICTATION EXERCISES IN DEVELOPING WRITTEN COMPETENCE IN FRENCH LANGUAGE TEACHING - Narzulloyeva Dilfuza Bahriddin qizi (Bright Mind Publishing, 2025)
Dictation exercises, once considered a traditional tool in language instruction, have recently garnered renewed interest for their pedagogical value in developing learners’ written competence. This study explores the role of dictation tasks in enhancing written expression among learners of French as a foreign language. Drawing on theoretical frameworks in second language acquisition and didactics, this research examines how various forms of dictation (e.g., standard, partial, interactive) contribute to vocabulary retention, grammatical accuracy, and syntactic coherence. An experimental approach was conducted with A2 level students, who participated in a series of targeted dictation exercises over four weeks. Pre- and post-intervention written assessments were analyzed to evaluate improvements in writing. The results indicate a statistically significant development in learners’ written performance, particularly in sentence construction and spelling accuracy. The findings support the inclusion of dictation as a structured component of writing instruction in foreign language pedagogy.
Keywords: Dictation, FFL, second language acquisition, writing skills, A2 learners.